2019
DOI: 10.1007/s10826-019-01543-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Externalizing Behavior of School-Age Boys: The Role of a Mother’s Mentalization and Attachment

Abstract: Objectives Externalizing behavior problems are considered to be a serious impediment to a child’s development, and therefore it is important to identify their predictors. In this study, we investigated the connections between school-aged boys’ externalizing problems, the mother’s reflective functioning (RF) and the mother’s perception of her childhood relationship with her own caregivers. Methods The study sample comprised 39 school-age boys diagnosed with externalizing behavior problems together with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Finally, albeit limited, there is evidence supporting the association between the role of mentalizing in the development of internalizing and externalizing problems (Sharp et al, 2008). Nonetheless, this evidence approaches the association from either a specific psychopathological condition (e.g., autism, sexual abuse, complex trauma, and borderline symptoms; e.g., Ensink et al, 2016) or a trans-generational point of view (i.e., maternal reflecting function moderating children externalizing difficulties; e.g., Ensink et al, 2017;Dejko-Wańczyk et al, 2020), or comprise a longitudinal design to analyze the trajectories of externalizing problems based on mentalizing variations (Morosan et al, 2020).…”
Section: The Lack Of Association Between Mentalization Polarities and Internalizing Or Externalizing Symptomsmentioning
confidence: 99%
“…Finally, albeit limited, there is evidence supporting the association between the role of mentalizing in the development of internalizing and externalizing problems (Sharp et al, 2008). Nonetheless, this evidence approaches the association from either a specific psychopathological condition (e.g., autism, sexual abuse, complex trauma, and borderline symptoms; e.g., Ensink et al, 2016) or a trans-generational point of view (i.e., maternal reflecting function moderating children externalizing difficulties; e.g., Ensink et al, 2017;Dejko-Wańczyk et al, 2020), or comprise a longitudinal design to analyze the trajectories of externalizing problems based on mentalizing variations (Morosan et al, 2020).…”
Section: The Lack Of Association Between Mentalization Polarities and Internalizing Or Externalizing Symptomsmentioning
confidence: 99%
“…In particular, disorganized attachment most strongly predicts EXT and avoidant attachment is most strongly associated with INT (Groh et al, 2017 ). In addition to attachment styles, caregiving behaviors including caregiver sensitivity and reflective functioning are associated with both EXT and INT (Carlone & Milan, 2020 ; Dejko-Wanczyk et al, 2020 ; Kok et al, 2013 ; Wang et al, 2013 ). Given the established links between quality of caregiving and attachment, attachment-based interventions have predominantly focused on evaluating changes in caregiver sensitivity and attachment security (e.g., Bakermans-Kranenburg et al, 2003 ).…”
Section: Attachment- and Emotion-focused Parenting Interventionsmentioning
confidence: 99%
“…Another study also found a relationship between secure attachment and children's behavioral adjustment problems (i.e. depression, anxiety, aggressive) (Ensink et al, 2019), A recent study demonstrated that children with poor attachment have higher risk of behavioral adjustment problems (Dejko et al, 2020). Furthermore, children raised by sensitive and responsible mothers tend to have fewer behavioral adjustment problems (Nunes et al, 2013).…”
Section: Maternal Attachment and Behavioral Adjustment Problemsmentioning
confidence: 93%